Experience of Electrical Design of Super Bunker of Coal Preparation Plant - YANG Feng-wei (Gong-kuang zidonghua, 2011)
In view of problem of hidden danger of coal bunker, taking super products bunker of one coal preparation plant as example, the paper introduced design methods in term of electrical safety prevention, electrical energy-saving and modular design of the bunker. The actual application showed that the design methods ensure safe and continuous production of coal preparation plant.